Influence of virtual reality on student learning in undergraduate construction education. Issue 4 (2nd October 2022) - Lucas, Jason; Gajjar, Dhaval
ABSTRACT: Virtual Reality (VR) allows for an active learning environment that can enhance a student's comprehension of material. This research explores the actual and perceived benefit of introducing a VR simulation into a materials and methods of construction course in undergraduate education. The study included the development and implementation of a virtual simulation environment to support learning in the materials and methods of construction course. Actual student performance was then compared between a control group, who did not use the simulation, and the intervention group, those who used the simulation. Other factors such as student self-efficacy, learning motivation, and technology acceptance for the intervention group were also examined. Findings suggest that students who utilized the simulation have a better understanding of the course material represented in the simulation compared to those that were only exposed to traditional course materials.